GENDER JUSTICE AS AN IMPETUS TO RENEWAL OF MORAL THEOLOGY - Xalxo, Prem (Asian Horizons, 2015)
In recent years, there has been a steep rise in the incidences of violence, atrocities and discrimination against women in India giving rise to heated debates on the issues of justice and equality in socio-cultural and religious ambit. The horrific stories of treating women as mere sex objects in some countries marred by war, conflicts and terrorism are raising still more serious questions regarding justice and human dignity. Contrary to some apprehensions regarding gender agenda as being focused on the destruction of sexes or of their duality or that of the two-parent family structure of mother and father, the debate on gender justice underlines the necessity of promoting equality between both sexes by eliminating deep-rooted bias, injustice and discrimination against women. Treating both men and women as created in the “image and likeness” of God (Gen 1:26) and giving equal importance to both sexes in socio-cultural and moral spheres could be an impetus to the renewal of moral theology in the light of the documents of the Second Vatican Council.